New edition of ao/ota fractions classification - Korzh, Mykola; Romanenko, Konstantin; Nikitin, Petro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
This article is devoted to the new classification of fractures according to the principles of AO (Arbeitsgemeinschaft Fur Osteosynthesefragen) and ОТА (Orthopedic Trauma Association). Presented short historical information about creation and spreading of classification of the long bones fractures. It is explained what was the authorʼs aim of the last compendium and why changes had happened. It was described the reasons why shaft fractures of type B1 and C1 were deleted from the classification, changes in the proximal shoulder and femoral fractures distribution. There was new approach to the classification of the two bone segments. Nowadays fractures of the forearm are divided separately, but ulnar and radial bones fractures are classified according to standard approach. It was shown the characteristics as for Monteggia та Galeazzi fractures. Similar is approach to crus fractures. There were new parts in the classification with universal modifications and characteristics. Authors gave examples how these new innovations can help to characterize bone muscles system more precisely. Classification of joints luxation with or without fractures was presented. It was presented to which localization we should concern isolated internal malleus or posterior tibia edge with intact (43В) or broken fibula (44). The new remarks as for fractures writing are described (absence of hyphen, appearance of the new signs in round and square brackets. The new approach as for sections with combined bone segments like broken wrist and foot. Names of classifications were included into compendium-2018, like periprosthetic fractures, injuries of spine, breast, ribs, scapula, pelvic ring and sacrum.